Penciptaan Karya Seni Lukis Kaca Dengan Teknik Layer - Isnanta, Satriana Didiek (Institut Seni Indoensia Surakarta, 2014)
Traditional glass painting in Indonesia are all just move the painting of medium canvas / cloth into the medium of glass. This makes traditional glass painting closed character of the medium. With this in mind it is ultimately the writer interested to study the creation of works of art glass to approach contemporary art discourse. Is expected to emerge glass paintings that have novelty or is present in the composition of the exploration areas, symbols, and meanings. In addition, this study also explores the creation of techniques, tools and materials work. Not only use metal paint painting techniques as well as traditional glass painting but using layer technique. This layer techniques to maximize the clarity of glass that had not explored in the practice of traditional glass painting.Keywords: Painting glass, experiment, layer technique